EXPERIMENTAL DEMONSTRATION OF THE TIMEIRREVERSIBLE THERMAL EVOLUTION PROCESS AND SOME OF ITS CONSEQUENCES - A. Titov; I. Malinovsky (European Scientific Journal, ESJ, 2014)
Using a recently developed technique of synchronous differential temperature measurements (Titov & Malinovsky 2005), the existence of the thermal surface energy (TSE) and of thermal hysteresis effect has been demonstrated in metallic gauge blocks (GB). The TSE (described here) is observed if there are inputs of energy and momentum of external electromagnetic (EM) field to material artefact and the heat source is not symmetrically located relative to the artefact surface. The TSE, linearly related to the Poynting vector of the EM field, presents the energy of the oriented motion of the coupled field-particles system inside artifacts. The TSE results in a thermal hysteresis effect, which is irreversible in time and has no symmetry in space. As the principle of superposition is shown not to be valid for EM fields in case of TSE, the hysteresis loop for the continuous sweep in time converts into a spiral, in which the form and the magnitude of the each cycle are slightly different from the ones of the adjacent cycles. In confirmation of the preceding theoretical result (Stroud et al 1972), the number of influence parameters in case of the field-particle system is found to be absolutely enormous, so that the thermal evolution process has, practically, infinite number of the existence and manifestation modes. Our studies present also an experimental confirmation of the basic results of the series of theoretical papers, initiated by R. H. Dicke (1954), in which the interaction of the ensemble of atoms with the electromagnetic field is analyzed.